Voluntary environmental agreements and competition policy: The case of Germany's private system for packaging waste recycling - Markus A. Lehmann (Fondazione Eni Enrico Mattei (FEEM), 2000)
The paper takes the viewpoint of the neoinstitutional theory of the firm to analyse Germany's voluntary Dual Management System for Packaging Waste Collection and Recycling (DSD); namely, its governance structure and its contractual relations with upstream and downstream firms. Two aspects crucial for assessing the antitrust implications of voluntary environmental agreements are highlighted. First, the institutional fine-tuning of a voluntary agreement matters when assessing its implications for market competition. Second, the design of the threat with respect to the instruments it prescribes is of crucial importance for the degree of centralisation and the anti-competitive impact of the private institutions that subsequently emerge.
Keywords: D62; D78; L22; L44; 330; Voluntary environmental agreements; antitrust; theory of the firm; waste management; Verpackungs-Recycling; Selbstverpflichtung; Konzentrationspolitik; Wettbewerbspolitik; Theorie der Unternehmung; Deutschland